Exchange rate behaviour in ASEAN countries: A sensitivity analysis - David Umoru; Beauty Igbinovia; Mohammed Farid Aliyu (The Central European Review of Economics and Management (CEREM), 2024)
Aim: The study examined the behavior of exchange rate in ASEAN countries. This was highly necessitated in order to account for the structural break in the data set occasioned by global financial crisis. Research method: The quantile regression sensitivity analysis was performed on daily series of exchange rate volatility for 8 ASEAN countries having divided our sample into two, before and after the financial crisis eras. Periods of low market volatility (2001-2006 plus 2010-2017) and high market volatility (1990-2000, 2007-2009, plus 2018-2023) correlate to the periods before and after the financial crisis, respectively. Findings: The empirical finding going forward is that since the global financial crisis took effect, exchange rate volatility has not been effectively curtailed by the governments and monetary authorizes of ASEAN countries especially in Thailand, Malaysia, Indonesia and Vietnam respectively. There is therefore the need for a policy fight in favour of stability of the currency exchange rates. Originality: The originality of the research resides with the sensitivity analysis which validates the presence of high persistence in the volatility of the Thai Baht exchange rate throughout the quantiles. This was followed on by the high persistence in the exchange rate of the Malaysian ringgit which began at the 70th quantile in the pre-financial crisis period with a persistence value of 1.0097 as against the 30th quantile in the post-financial crisis estimations with a persistence value of 1.0387. The Indonesian Rupiah and Vietnamese dong took turns as regards volatility persistence. We also found significant ARCH effect which instigated further estimations of the GARCH and FIGARCH models as robustness checks. Contributions: With the GARCH results, the study contributed to establishing persistence of volatility in the exchange rates of all ASEAN countries in our sample, with varying degrees and this could be attributed instabilities in the economies. Explicitly, the significance of the FIGARCH coefficient confirms the persistence of volatility over time with considerable long-term memory effect. This implies that once the exchange rate becomes volatile, such volatility last long, influencing future volatility levels noticeably in all the countries. Exchange rate volatility persistence of the Singapore Dollar was very low.
Keywords: A20; B34; C50; 330; Exchange rate behavior; FIGARCH-DCC; volatility persistence; RER; long-term memory; volatility